Measuring Self-Efficacy in English for Specific Purposes: A Case Study of Engineering Students - Diana, Apriana (English Language in Focus (ELIF), 2025)
This descriptive statistical study assesses students' perceptions of their self-efficacy in English for Specific Purposes (ESP). The study involved 40 students from the Mechanical Engineering program at the Faculty of Engineering, Universitas Muhammadiyah Jakarta. Data were collected using a 5-point Likert scale questionnaire, adapted and modified from Kosimov (n.d.), and distributed via Google Forms after undergoing face validity assessment. The data were analyzed using simple percentage calculations and presented descriptively. The findings indicate that the majority of students held a positive perception of their self-efficacy in ESP, as evidenced by the highest response rate for the "agree" option (64.8%), followed by "strongly agree" (14.2%). Furthermore, the analysis suggests that most students demonstrated optimism, high self-efficacy, and a strong commitment to excelling in ESP learning relevant to their field of study.